Research and application of MEC service continuity technology - Lei MAO; Weibin WANG; Jian LUO (Dianxin kexue)
The current mobility problems and feasible solutions were analyzed,and the existing service continuity capabilities and key features on the network-side which were defined by 3GPP were studied,including SSC mode,uRLLC,traffic routing and so on.A network-side and application-side collaboration mechanism was proposed to satisfy the low latency services involving cross-MEC handover for fast mobility at the edge scenarios.The general idea of the follow-up study on mobility management and the path of phased implementation were also proposed.